Persepsi Umat Buddha di Temanggung, Pati, Dan Banyumas Mengenai Kompetensi Penyuluh Agama Buddha Profesional - Madiyono Madiyono; I Ketut Damana; Even Even (Jurnal Pelita Dharma, 2018)
The preservation of Buddhism in Indonesia is greatly influenced by competent and profesional counselors so that the quantity of Buddhists can also increase. In some regions the number of Buddhists experiences ups and downs, along with dedication of Buddhist councelors, assemblies, and the Sangha. Related to this, efforts were made to gather information on various competency of counselors needed by Buddhists in Temanggung, Pati, and Banyumas Districts.Data collection was done in a qualitative way using in-depth interviews, observation, and documentation. Data were analyzed using the Miles and Huberman model. The credibility of the data was done by triangulation, member check, and increasing perseverance.The results of the study show that in general, Buddhists in Central Java understand the duties, roles and functions of Buddhist councelors. The competencies expected by Buddhists in Central Java cover many aspects. Competencies possessed by counselor include: capable to speak in public, capable of preparing guidance material well, master the basic principles of Buddhism, competence in delivering the teaching of the Buddha well, skillfull in carrying out devotional service (rites), competent in applying appropriate methods, skillfull in counseling lay-people. Buddhist councelors must have abilities in other fields, such as: law, the development of social political situations, governance, good communication. In terms of attitude, the councelors must also be able to be role models, be able to maintain harmony between Buddhists and other people of religion. In addition, the councelors must also be competent, humorous, non-sect, responsive, disciplined, diligent, good, open, willing to accept criticism, firm, adjust the condition of the people. Buddhist councelors must be neutral, also expected to have the ability to understand the latest informations, be able to operate a laptop, and other telecommunication and information tools, be able to preserve local culture, such as playing gamelan, singing Badrasanti and singing Javanese Buddhist songs.Pelestarian agama Buddha di Indonesia sangat dipengaruhi oleh penyuluh yang kompeten dan profesional sehingga jumlah umat Buddha juga dapat meningkat jumlahnya. Di beberapa daerah, jumlah umat Buddha mengalami pasang surut, seiring dengan jumlah penyuluh agama Buddha, majelis, dan Sangha. Sehubungan dengan hal tersebut, dilakukan upaya untuk mengumpulkan informasi tentang berbagai kompetensi penyuluh yang dibutuhkan oleh umat Buddha di Kabupaten Temanggung, Pati, dan Banyumas.Pengumpulan  data  dilakukan  secara  kualitatif menggunakan  wawancara  mendalam,  observasi,  dan dokumentasi. Data kemudian dianalisis menggunakan  model Miles dan Huberman. Kredibilitas data dilakukan dengan triangulasi, cek anggota, dan meningkatkan ketekunan.Hasil penelitian menunjukkan bahwa secara umum, umat Buddha di Jawa Tengah memahami tugas, peran  dan  fungsi dewan agama Buddha. Kompetensi yang diharapkan oleh umat Buddha di Jawa Tengah mencakup banyak aspek.  Kompetensi yang dimiliki oleh penyuluh agama Buddha meliputi: kemampuan berbicara di depan umum, mampu menyiapkan bahan bimbingan dengan baik, menguasai prinsip-prinsip dasar agama Buddha, kompetensi dalam menyampaikan ajaran Buddha dengan baik, terampil dalam melaksanakan pelayanan ritual (ritus), kompetensi dalam menerapkan metode yang tepat, keterampilan dalam konseling umat awam. Penyuluh Agama Buddha juga harus memiliki kemampuan di bidang lain, seperti: hukum, memahami perkembangan situasi sosial politik, pemerintahan, dan keterampilan komunikasi yang baik. Dari segi sikap, penyuluh agama Buddha juga harus bisa menjadi panutan, mampu menjaga keharmonisan antara umat Buddha dan umat beragama lainnya. Selain itu,penyuluh juga harus kompeten, humoris, bersikap non- sekte, responsif, disiplin, rajin, baik, terbuka, mau menerima kritik, tegas, dan dapat beradaptasi dengan kondisi masyarakat. Penyuluh Agama Buddha selain bersikap netral juga diharapkan memiliki kemampuan untuk memahami perkembangan informasi terbaru, dapat mengoperasikan laptop dan alat telekomunikasi dan informasi lainnya, dapat melestarikan budaya lokal, seperti bermain gamelan, menyanyi Badrasanti dan menyanyikan lagu- lagu Buddha Jawa.